Control of Essential Commodities Act, 1956 : containing black marketing, anti-hoarding, smuggling, profiteering, gold control, and other control orders - Mohsin, I. M. M. (Universal Books : Available at Book Syndicate, 1991)
Includes related acts, ordinance, and orders.